A systematic review of pharmacological activities and safety of Moringa oleifera - Jacob O. Popoola; Oluwadurotimi S. Aworunse; Olusola L. Oyesola; Olayemi O. Akinnola; Olawole O. Obembe (Shahrekord University of Medical Sciences, 2020)
In the last few decades, Moringa oleifera, a multipurpose medicinal plant (MMP) has received increased research attention and commercial interest for its nutritional, therapeutic and pharmacological properties. Rigorous approaches including biological assays, animal and clinical trials are required towards safe usage as herbal therapy. We conducted a systematic review of the known pharmacological activities, toxicity, and safety of M. oleifera, usually used locally in the treatment and prevention of myriads of illnesses. Five major bibliographic databases (SCOPUS, Web of Science, Science Direct, PubMed, and Mendeley) were searched for studies reported on pharmacological activities, toxicity, and safety assessment of M. oleifera in the last 29 years (1990 - 2019). Studies on animals and humans involving aqueous leaf extracts and different preparations from M. oleifera seed and bark were also considered. All articles retained, and data collected were evaluated based on the period of the article, country where such studies were conducted and the document type. Our search results identified and analyzed 165 articles while 63 studies were eventually retained. Diverse pharmacological activities including neuroprotective, antimicrobial, antiasthmatic, anti-malaria, cardioprotective, antidiabetic, antiobesity, hepatoprotective and cytotoxic effects, amongst others, were recorded. Toxicity studies in animal models and few human studies showed that M. oleifera is safe with no adverse effect reported. The importance of the plant is highlighted in the search for new bioactive compounds to explore its therapeutic potentials towards drug discovery and development in the pharmaceutical and allied industries.